Kurortinio sveikatingumo plėtra sovietmečiu: Palangos atvejis (1945–1990) - Kučinskaitė, Eglė (Vilnius University Open Series, 2025)
The article explores the peculiarities of the Soviet-era Palanga resort architecture and wellness services. The importance of social architecture for health development shall be analysed, and the conditions of visitors in nomenclature villas and trade union-dependent sanatoriums and holiday homes shall be compared. The study explained the ideological wellness program, which showed the Government’s desire to form a recreation accessible to the masses with a pass system. In addition, by referring to archival documents, the study discusses how different features of the resort architecture and wellness services were reflected in political and trade-based building charter resorts, thus highlighting social inequalities and different recreation policies.
Keywords: kurortas; Palanga; sveikatingumas; nomenklatūra; profsąjunga; kurortinė architektūra; poilsio namai; sovietmetis